1984
DOI: 10.1002/lsm.1900040104
|View full text |Cite
|
Sign up to set email alerts
|

Photoradiation therapy of endobronchial lung cancers employing the photodynamic action of hematoporphvrin derivative

Abstract: Thirty-five patients with tumors within the tracheobronchial tree were treated with photoradiation therapy (PRT) employing the photodynamic action of hematoporphyrin derivative (HPD). An effective protocol has been developed consisting of 3.0 mg/kg HPD given intravenously 72 hours prior to the bronchoscopic illumination of the endobronchial tumor sites with red light (630 nm) from an argon pumped dye laser. Light applicators were developed that provided surface (area) and insertion (volume) illumination of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(39 citation statements)
references
References 4 publications
0
38
0
1
Order By: Relevance
“…PDT using the photosensitiser haematoporphyrin derivative (HPD) has been shown to be effective in the treatment of cancers in various sites including skin (Dougherty, 1987), bronchus (Balchum, 1984) and bladder (Nseyo, 1992), often after more conventional treatments have failed. The cytoxicity of HPDmediated PDT has been attributed to the production of reactive oxygen species, although the precise mechanism of damage is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…PDT using the photosensitiser haematoporphyrin derivative (HPD) has been shown to be effective in the treatment of cancers in various sites including skin (Dougherty, 1987), bronchus (Balchum, 1984) and bladder (Nseyo, 1992), often after more conventional treatments have failed. The cytoxicity of HPDmediated PDT has been attributed to the production of reactive oxygen species, although the precise mechanism of damage is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest article that qualified for inclusion was published in 1984 [3] and the latest was dated 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Long-term (5-yr) survival amongst patients with TIS and stage 1, who responded fully to treatment, has beeny70% [2]. When death from causes other than cancer was eliminated 5-yr survival of 90% was recorded in treatment of TIS tumours [2]; 4) PDT in bronchial stump recurrence of cancer was reported in three series [2,3,15]. LAM [13] found that three of the five patients with recurrence of cancer at the bronchial stump who initially responded to PDT had tumour recurrence.…”
Section: Group 2: Photodynamic Therapy In Patients With Early Stage Lmentioning
confidence: 99%
“…Nevertheless, by virtue of its high incidence, advanced stage of disease at presentation and highly unresectable rate, lung cancer became one of the first cancers to be targeted for PDT trials [82][83][84][85].…”
Section: Therapeutic Bronchoscopy Of Lung Cancers J-m Vergnon Et Almentioning
confidence: 99%
“…18). The initial trial of bronchoscopic PDT in the 1980s was directed towards symptomatic patients with endoluminal exophytic tumours causing major obstruction [83]. In the light of subsequent and more recent experience, PDT indications in this group have become more stringent.…”
Section: Group a Patientsmentioning
confidence: 99%